Case study in SenseCam use as an intervention technology for early-stage dementia. (1st January 2012) - Piasek, Paulina; Irving, Kate; Smeaton, Alan F.
Dementia is a growing concern with an estimated 41, 740 in Ireland and 35.6 million people living with dementia worldwide. In the absence of a medical cure for dementia, pervasive technologies are emerging to support people with dementia. Among such applications is lifelogging, which involves continuously wearing technology to capture a large part of the wearer's life emerging. The recorded data allows clinicians and others to detect behaviour changes or help in memory recall. This study explores the use of SenseCam lifelogging technology as a therapeutic intervention for people with early stage dementia. Based on the principles of cognitive stimulation therapy (CST) it aims to engage them in meaningful discussions about their recent past as captured in the SenseCam images. These discussions offer potential to help maintain the person's identity. The preliminary findings from the first case study highlight some functional issues of SenseCam use within CST principles.